The Implementation and Challenges of the Triage System in Managing Catastrophic Disease Emergencies in Hospitals: Implementation and Challenges of the Triage System in Managing Catastrophic Disease Emergencies in Hospitals - Ajartha, Ronny (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Emergency management of catastrophic illnesses in hospitals requires an effective and efficient triage system to ensure that critically ill patients receive prompt and appropriate care. This article discusses the implementation and challenges faced in implementing a triage system in a hospital environment. This study used a qualitative method with data collection through in-depth interviews, observations, and literature studies. The results showed that, although the triage system has been successful in improving the response to emergencies, there are several challenges that need to be addressed, including limited resources, lack of adequate training for medical personnel, and communication gaps between departments. Recommendations for improvement include increasing staff training, providing additional resources, and developing better communication protocols. This study is expected to provide insights for policy makers and medical practitioners in improving the quality of emergency management of catastrophic illnesses in hospitals.